Designing in Ivory and White : Suzanne Perron Gowns from the Inside Out - Perron, Suzanne (Book collections on Project MUSE., 2012)
The name "Suzanne Perron" is synonymous with exquisite detail. Her expertly tailored gowns-worn at the elaborate balls of Mardi Gras and down the aisle at New Orleans weddings-draw from the legacy of couture design. After years working alongside Vera Wang, Carolina Herrera, Anna Sui, and Ralph Rucci in New York, Louisiana native Perron returned home in 2005 to open her own custom design business, specializing in once-in-a-lifetime gowns for brides, debutantes, and Mardi Gras royalty. Designing in Ivory and White captures the rise of this talented designer, from her first Singer sewing machine.